Tuberculous Pleural Effusion in Child with Acute Lymphoblastic Leukemia - Diska Yulia Trisiana; Finny Fitry Yani (Science Midwifery, 2021)
Tuberculosis (TB) is a world health problem, especially in developing countries. Extrapulmonary tuberculosis may occur in 25-30% of TB infected children. Immunocompromised patientsare in risk for developing TB disease, such as in malignancy. In this case, we will present pleural TB case in children with acute lymphoblastic leukemia with a history of previous pulmonary TB. This aims to highlight the diagnostic points of pleural effusion due to malignancies or reactivation of latent infection. A 16 years old boy had been known to have an acute L2 lymphoblastic leukemia and history of pulmonary TB at 6 years old and recovered. Patient has recurrent fever, weight loss, and shortness of breath. Chest pain and decrease of breath sound at left hemithorax were found in physical examination. Chest x-ray showed left pleural effusion. Pleural tapping was performed and showed mononuclear predominant, indicated TB or malignancy. Adenosine deaminade (ADA) test was performed, it confirmed the diagnosis of TB pleural effusion. Patient received anti tuberculosis therapy plus prednisone.n Diagnosing TB in malignancies is challeingchallenging due to similarity of clinical manifestation, and patient with malignancy are in high risk for developing TB infection. ADA pleural test has a higher specificity and sensitivity in diagnosing pleural TB.